Potentiometric Determination of Duloxetine Hydrochloride Using Coated Wire Electrode in Pure and Pharmaceutical Preparations - Al-Qahtani, Salhah D. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: An electrode of coated wire duloxetine-selective type was prepared and categorized in aqueous solution as a sensor for duloxetine hydrochloride (DLX) determination and in pharmaceutical preparations by the standard addition method, at 25°C. Materials and Methods: Local drug stores were the pharmaceutical preparations containing DLX (Cymbalta®, 60 mg DLX/capsules and Yentreve®, 20 mg DLX/capsules). Potentiometrically, DLX was determined by standard addition method utilizing the investigated electrode. Standard DLX solution in small increments 1.0 × 10−2 M was added to 50 mL aliquot samples of various drug concentrations in the standard addition method. Variation in potential reading at a constant temperature of 25°C was documented for each increment and used to calculate the drug sample solution concentration. Results and Discussion: The electrode shows a linear response with slope of 59.0 mV per duloxetine concentration decade for optimum electrode 9.0% at 25°C ± 0.1°C when pH of test solution was in the range of 4.0–9.0at with potentiometric responses were independent. In the presence of different inorganic cations, sugars and amino acids that electrode shown good selectivity for DLX. It was successfully used for potentiometric determination of DLX both in pure solutions and in pharmaceutical preparations. Conclusion: According to membrane electrode of the coated wire type, the DLX exhibited advantages of simple design and operation, reasonable selectivity, and fast response. Further, the electrode can be used by direct pure form potentiometry and in pharmaceutical preparations to DLX determination.